Millimeter-wave coplanar stripline power dividers. Issue 3 (1st May 2013) - Li, Chong; Lok, Lai Bun; Khalid, Ata; Papageorgiou, Vasileios; Grant, James; Cumming, David R. S.
Abstract : We present the design, fabrication, and measurement of a 2-way modified Wilkinson divider constructed in a coplanar geometry exhibiting ultra wideband isolation, transmission, and port matching in the millimeter-wave frequency range. The proposed divider replaces the lumped resistor in the conventional Wilkinson divider with two quarter-wave length transmission lines, a phase inverter, and two 2Z0 resistors. Except for the three ports that are coplanar waveguides (CPWs), the main body of the divider uses coplanar striplines (CPS). The phase inverter is realized using a simple airbridge-based crossover which is compatible with a modern monolithic microwave integrated circuit process. The divider has a ring-like configuration fabricated on a 620 µm thick semi-insulating GaAs wafer using electron beam lithography (EBL) technology. Three-dimensional (3D) full-wave electromagnetic simulations have been carried out to optimize the design and investigate the possible effect of fabrication tolerance on the performance of the crossover and the divider. Two dividers working at center frequencies of 25 and 80 GHz have been designed, fabricated, and tested. They all show consistent performance in terms of bandwidth, isolation, and port matching. Experimental and simulation results are in excellent agreement.